Creativity and Innovation of Artist in Maintaining and Developing the Songah Tradition Art (Harmonia: Journal of Arts Research and Education, 2020)
Songah is one of the traditional arts originating from Citengah Village, Sumedang Regency. This art was formed from the creativity and innovation of the people of Citengah Village, Sumedang Regency to maintain the existence of traditional arts. Based on concern and love for their culture, the community continues to make reforms so that the existence of the songah art is maintained and can keep up with the times. This study aims to describe and analyze the creativity and innovation of society in utilizing existing natural resources as an effort to maintain and develop the songah traditional art. Through a qualitative approach and descriptive methods, the researchers reveal the creative process carried out by the people of Citengah Village in maintaining and developing the songah art. This study’s data were collected through observation, interviews, and strengthened by a literature review, which was then analyzed using descriptive qualitative techniques. The results showed that the creativity of the people of Citengah Village in maintaining and developing the songah traditional art can be seen in the aspects of natural resource management in the area. The community changed songong, which is a means of blowing fire in a furnace (Sundanese: Hawu), into an art tool called songah (songsong Citengah/songong kabungah). As a musical instrument having no tone, people who are members of the community collaborate songsong with other musical instruments to produce a unique musical composition. The development of the s art cannot be separated from the innovation of the community that collaborates songah with other musical instruments. This has a positive impact on the songah art so that it can be side by side and not less competitive with other traditional arts, including arts originating from abroad. Based on the results of existing research, the development of community’s creativity and innovation in maintaining the existence of art needs to be done continuously to anticipate being alienated and the loss of traditional arts.